PENGARUH DEBT TO EQUITY RATIO DAN EARNING PER SHARE TERHADAP HARGA SAHAM PADA INDUSTRI MANUFAKTUR KONSUMSI YANG TERDAFTAR DI BEI PERIODE 2006 – 2008 - Oktafalia Marisa (Business Management Journal, 2017)
Every industry in financial market has a same goal, which is an optimum stock price. We’ve known there are a lot of factor effected stock price, such as fundamental structur, demand and supply law, interest rate, devidend and news and rumors. The research objective is to find out the effect od Debt Equity Ratio (DER) and Earning Per Share (EPS) to Stock Price. The subject of this research is the manufactur company in consumption sector listed in Bursa Efek Indonesia (BEI) frim 2006 to 2008. The results of this research are, there is no effect od DER to stock price if EPS constant, but there is effect of DER and EPS to stock price hopefully this research could provided a comprehensif data to develop any research in future.Keywords : Debt to equity ratio, EPS, stock price